Inter-local Water Agreements : Law, Geography, and NAFTA - Forest, Patrick (Les Cahiers de droit, 2010)
The North American Free Trade Agreement (NAFTA) has not only promoted free trade and intensified trading between the Parties to the agreement, it has also instigated passionate debates in regards to the legal status of water. The only existing water transfers between Canada and the United States have yet to be fully investigated, this despite the abundant literature dedicated to bulk water transfers. Transboundary local water supplies agreements between borderland communities have existed for many decades. However, in the context of NAFTA, a better understanding of the legal ramifications of these transfers for Canada is necessary. The aim of this paper is to introduce the concept of transboundary local water supplies and to establish whether or not they constitute a threat to Canada. The analysis is based on an interdisciplinary approach that draws upon literature from both geography and law. This paper stresses that these water transfers are not water exports under NAFTA, and do not represent a threat to Canada’s water resources.